The Translation of Lexical Collocations in Undergraduate Students’ Theses’ Abstract: Students Versus Google Translate - Clara Herlina Karjo; Ecclesia Metta (Lingua Cultura, 2019)
This research intended to compare the translations of lexical collocations found in the abstract section of students’ theses. The purposes were to find out the errors in translating lexical collocation either by Google Translate or student translator. The data were taken from twenty working papers of English Literature students at Binus University. The abstracts of these theses (in English and Indonesian) were then processed with Google Translate. Thus, there were four sets of data to analyze: (1) Students’ Text in Indonesian (STI), (2) Google Translate of STI in English (GTE), (3) Students’ Text in English (STE), and (4) Google Translate of STE in Indonesian (GTI). From the data, samples of collocations were taken and categorized based on Hill’s classification of lexical collocations. The lexical collocations found in the four sets of data were scrutinized, compared, and analyzed to find the errors in forms and meaning as well as in the translation. The results reveal that errors in translating collocations are mostly made by Google Translate rather than the students. This research implies that Google Translate still needs improvement in translating collocations, but it is also possible that translation errors occur because of students’ misuse of collocation.